Decompositions of Analytic 1-Manifolds - Hanusch, Maximilian (Indagationes Mathematicae.)
Keywords: Lie group actions and analytic 1-submanifolds

Rezension zu Martin Breul/Klaus Viertbauer (Hg.), Der Glaube und seine Gründe, Tübingen: Mohr Siebeck 2022, brosch. - Dorogova, Elizaveta (Theologie und Glaube)

Promoting multilingual practices in school and home environments - Szczepaniak-Kozak, Anna; Farrell, Angela; Ballweg, Sandra; Daase, Andrea; Wąsikiewicz-Firlej, Emilia; Masterson, Mary

Aus Erklärvideos lernen - Kulgemeyer, Christoph; Sterzing, Fabian; Hörnlein, Madeleine (Digital Physik unterrichten. Grundlagen, Impulse, Perspektiven)

Comparative Study of the Influence of Heat Treatment and Additive Manufacturing Process (LMD & L-PBF) on the Mechanical Properties of Specimens Manufactured from 1.2709 - Gnaase, Stefan; Niggemeyer, Dennis; Lehnert, Dennis; Bödger, Christian; Tröster, Thomas (Crystals)
(1) This work answers the question of whether and to what extent there is a significant difference in mechanical properties when different additive manufacturing processes are applied to the material 1.2709. The Laser-Powder-Bed-Fusion (L-PBF) and Laser-Metal-Deposition (LMD) processes are considered, as they differ fundamentally in the way a part is manufactured. (2) Known process parameters for low-porosity parts were used to fabricate tensile strength specimens. Half of the specimens were heat-treated, and all specimens were tested for mechanical properties in a quasi-static tensile test. In addition, the material hardness was determined. (3) It was found that, firstly, heat treatment resulted in a sharp increase in mechanical properties such as hardness, elastic modulus, yield strength and ultimate strength. In addition to the increase in these properties, the elongation at break also decreases significantly after heat treatment. The choice of process, on the other hand, does not give either process a clear advantage in terms of mechanical properties but shows that it is necessary to consider the essential mechanical properties for a desired application.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

HIEF: a holistic interpretability and explainability framework - Kucklick, Jan-Peter (Journal of Decision Systems)
Many applications are driven by Machine Learning (ML) today. While complex ML models lead to an accurate prediction, their inner decision-making is obfuscated. However, especially for high-stakes decisions, interpretability and explainability of the model are necessary. Therefore, we develop a holistic interpretability and explainability framework (HIEF) to objectively describe and evaluate an intelligent system’s explainable AI (XAI) capacities. This guides data scientists to create more transparent models. To evaluate our framework, we analyse 50 real estate appraisal papers to ensure the robustness of HIEF. Additionally, we identify six typical types of intelligent systems, so-called archetypes, which range from explanatory to predictive, and demonstrate how researchers can use the framework to identify blind-spot topics in their domain. Finally, regarding comprehensiveness, we used a random sample of six intelligent systems and conducted an applicability check to provide external validity.
Keywords: Explainable AI (XAI); machine learning; interpretability; real estate appraisal; framework; taxonomy

Sprachsensibles Arbeiten mit Hadithen im Islamischen Religionsunterricht - Kamcili-Yildiz, Naciye (Hadithdidaktik im Diskurs)

Was heißt religiöses gebildet? Konzepte religiöser Bildung von islamischen Religionspädagogen - Kamcili-Yildiz, Naciye; Tautz, Monika (Islamunterricht im Diskurs. Religionspädagogische und fachdidaktische Ansätze)

Radiocarbon Dating Of Manuscripts Kept in the Central Library of the University of Tehran - Aghaei Abrandabadi, Seyed Ali; Bahrololoumi, Faranak; Hajdas, Irka; Jafarian, Rasul; Kordavani, Lili; Marx, Michael

The Hermeneutics of al-Sharīf al-Murtaḍā (d. 436/1044) in the interpretation of Akhbār al-Āḥād in his Kitāb al-Amālī - Aghaei Abrandabadi, Seyed Ali (Hadith Commentary: Continuity and Change)

The Black Humanist Tradition in Anti-Racist Literature: A Fragile Hope - Hartmann, Alexandra

Wie digitale Medien die kommunikative Aushandlung von Freundschaften verändern - Teichert, Jeannine

Mediale Identitätsaushandlungen deutscher MigrantInnen im Zuge des Brexit - Teichert, Jeannine; Meister., D.M. (MedienPädagogik)

Two Sparsification Strategies for Accelerating Demand-Driven Pointer Analysis - Karakaya, Kadiray; Bodden, Eric (2023 IEEE Conference on Software Testing, Verification and Validation (ICST))

Digitale Transformation im Theater – Mittels Besucherforschung und Entscheidungsunterstützung zur besseren Angebotsgestaltung - Kempkes, Jens Peter; Kreuzhage, Katharina; Kundisch, Dennis; Seutter, Janina; Weskamp, Christoph

Lösungsstrategien für das Halbhohlstanznieten von höchstfesten und ultrahöchstfesten Stählen mit Aluminiumwerkstoffen - Uhe, Benedikt; Meschut, Gerson
Aufgrund der Leichtbauweise von Fahrzeugkarosserien werden konventionelle Stahlgüten durch ultrahöchstfeste Stahlwerkstoffe ersetzt. Die hohe Festigkeit dieser Werkstoffe stellt eine Herausforderung für das mechanische Fügen dar. Weil diese Stahlwerkstoffe zunehmend in erhöhter Dicke eingesetzt werden, wird die Leistungsfähigkeit konventioneller Halbhohlstanzniete überschritten. Im Rahmen des Forschungsvorhabens wurde ein Stanzniet erarbeitet, welcher eine Erweiterung des Einsatzbereichs des Halbhohlstanznietens auf stempelseitige Fügeteile aus höchstfesten und ultrahöchstfesten Stahlwerkstoffen bei großer Materialdicke ermöglicht. Zunächst wurden Referenzverbindungen mit handelsüblichen Stanznieten erstellt und analysiert. Durch die simulationsgestützte Ermittlung der Spannungs- und Dehnungsverhältnisse im Stanzniet wurden Ansätze für die Modifizierung der Stanzniete erarbeitet. Ebenso wurde der Einfluss der einzelnen Geometrieparameter des Stanzniets auf die Verformung des Stanzniets und die Verbindungsausbildung untersucht. Parallel dazu, wurden die mechanischen Eigenschaften potenzieller Stanznietwerkstoffe charakterisiert und eine angepasste Wärmebehandlungsstrategie erarbeitet. Durch die Modifizierung der Werkstofflegierung und der Wärmebehandlung kann eine Erhöhung der Festigkeit des Stanznietwerkstoffs um ca. 20 % gegenüber der bisher üblichen Härteklasse H6 erreicht werden. Daher kann eine Stanznietgeometrie mit einem bisher üblichen Nenndurchmesser von 5,5 mm verwendet werden. Die neuen Stanzniete wurden experimentell in einem zweistufigen Kaltumformprozess hergestellt. Abschließend wurde die erarbeitete Lösung basierend auf experimentellen Versuchen analysiert.

Förderung von digitalisierungsbezogenen Kompetenzen von angehenden Physiklehrkräften mit dem SQD-Modell im Projekt DiKoLeP - Weiler, David; Burde, Jan-Philipp; Große-Heilmann, Rike Isabel; Lachner, Andreas; Riese, Josef; Schubatzky, Thomas (Lehr-Lern-Labore und Digitalisierung)

The Impact of the German Fuel Discount on Prices at the Petrol Pump - Seiler, Volker; Stöckmann, Nico (German Economic Review)
Abstract This paper investigates the price impact of the fuel discount in Germany, which was introduced between June and August 2022 to partially compensate increased energy costs. Using the augmented synthetic control method (ASCM) to construct the counterfactual, we provide quantitative evidence to the heated debate concerning the impact of this policy tool and find the fuel discount to have decreased consumer prices of petrol (diesel) by at least 0.30 euro per litre (0.10 euro per litre) on average. The results are robust to various sensitivity checks. Thus, oil companies and petrol stations decreased prices for consumers and passed on about 85 % (65 %) of the discount in case of petrol (diesel). Moreover, we do not find signs of excessive price increases in anticipation of the fuel discount.
Keywords: Economics and Econometrics

Von der "Shallowing Hypothese" zur "Illusion of Understanding" -wie wirken Erklärvideos und Lehrbuchtexte auf Wissen und Verstehensillusion? - Kulgemeyer, Christoph; Sterzing, Fabian; Hörnlein, Madeleine

"Aus Erklärvideos lernt man nur oberflächlich" - oder erwirbt man auch Konzeptwissen? - Hörnlein, Madeleine; Kulgemeyer, Christoph